Percutaneous Coronary Intervention in Patients With Diabetes: Current Concepts and Future Directions - Armstrong, Ehrin J. (J Diabetes Sci Technol, 2014)
Patients with diabetes and coronary artery disease represent a challenging and growing subset of the population. Although surgical revascularization is the preferred treatment for patients with diabetes and multivessel coronary artery disease with stable angina, a significant proportion of diabetic patients undergo percutaneous revascularization due to comorbidities, presence of single-vessel disease, or presentation with myocardial infarction. The development of drug-eluting stents has significantly improved the results of percutaneous revascularization among diabetic patients, but a number of challenges remain, including higher rates of restenosis and stent thrombosis among diabetic patients. With current technologies, the outcomes of diabetic patients treated with noninsulin agents have approached that of nondiabetic patients. In comparison, patients with diabetes who require insulin therapy represent a high-risk cohort with increased rates of target vessel failure after coronary revascularization. The development of bioresorbable stents and new drug elution systems may provide additional future benefit among patients with diabetes undergoing percutaneous coronary artery revascularization.